Athermal Tantalum Pentoxide Mach-Zehnder Interferometers Based on Structural Compensation Method - Mingjian You; Zhenyu Liu; Weiren Cheng; Xingyu Tang; Ning Ding; Zhengqi Li; Min Wang; Li Shen; Qiancheng Zhao (IEEE Photonics Journal)
We demonstrate Mach-Zehnder interferometer-based (MZI) athermal photonic devices using the structural compensation method. Unlike previous structural compensation studies that were applied on the thermal sensitive materials such as silicon, this work is implemented in tantalum pentoxide (Ta2O5) platform whose thermo-optic coefficient is low. This allows us to achieve ultra-athermalized filters by combining the structural compensation method and the material's own thermo-optic properties. Two types of devices are proposed: the asymmetric Mach-Zehnder interferometer (AMZI) and the ring-coupled Mach-Zehnder interferometer (RMZI). The temperature-dependent wavelength shift (TDWS) of the AMZI device is only 1.98 pm/K around 1550 nm which is 4.6 times smaller than a regular MZI. The TDWS remains below 2.23 pm/K across a broad bandwidth from 1480 nm to 1580 nm. By breaking the linear dependence between the wavelength shift and the temperature change, the maximum resonance drift can be restricted by using a ring-coupled MZI. Owning to Fano effect, the transmission spectrum of the RMZI device exhibits an oscillating behavior when facing temperature changes. This work proves the effectiveness of structural compensation method on an already low thermo-optic photonic platform, paving the way towards realization of ultra-athermal integrated optical filters in a low-loss and CMOS-compatible platform.